New technologies and enforced disappearances: opportunities and challenges for the protection of human rights - Vesna Stefanovska (Revija za kriminologiju i krivično pravo)
New technologies and enforced disappearances have been part of thematic study included in the annual report of the Working Group on Enforced and Involuntary Disappearances (WGEID) published in August 2023. Enforced disappearances present flagrant human rights violation where the families of disappeared person are not familiar with the fate and whereabouts of their disappeared relatives. The use of new technologies in cases of enforced disappearances may enhance the human rights protection, facilitate the search for disappeared persons and obtain evidence. However, new technologies can be used to prevent further investigations and obtain evidence especially in cases where torture is committed by state actors and cases of enforced disappearances in transnational context. This paper will analyze the positive and negative effects from the use of new technologies in enforced disappearances and will emphasize the importance to conduct an effective investigation and to acknowledge the right to truth in these cases.